2017
DOI: 10.1037/dev0000391
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of emotional and behavioral problems in a low-income, Mexican American sample.

Abstract: Clinically meaningful behavior problems are thought to be present beginning in the early toddler years, yet few studies have investigated correlates of behavior problems assessed before age 2 years. The current study investigated the direct and interactive contributions of early infant and caregiver characteristics thought to play an important role in the ontogeny of behavior problems. Specifically, the study examined: (a) the links between infant temperamental reactivity and toddler behavioral symptoms, (b) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…Elevated maternal stress hormones and other stress‐related physiological changes may affect fetal neurodevelopment directly or through epigenetic processes, impacting the structure and function of brain areas important to the developing stress response and future behavior (Bale, ; Charil, Laplante, Vaillancourt, & King, ; Glover, O'Connor, & O'Donnell, ; Monk, Spicer, & Champagne, ). In humans, prenatal maternal stress (PNMS) has been operationalized variably as psychological distress (e.g., pregnancy‐specific anxiety or depressive symptoms) or stressful life events (e.g., bereavement, daily hassles), with evidence of associations with increased emotional, behavioral, and social problems in childhood (Lahti et al., ; Lin, Crnic, Luecken, & Gonzales, ; O'Connor, Heron, Golding, Beveridge, & Glover, ; Robinson et al., ). Nevertheless, despite these associations, conjecture remains concerning the mechanisms and moderators of the influence of PNMS on infant and child outcomes.…”
Section: Natural Disasters As “Natural Experiments”mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated maternal stress hormones and other stress‐related physiological changes may affect fetal neurodevelopment directly or through epigenetic processes, impacting the structure and function of brain areas important to the developing stress response and future behavior (Bale, ; Charil, Laplante, Vaillancourt, & King, ; Glover, O'Connor, & O'Donnell, ; Monk, Spicer, & Champagne, ). In humans, prenatal maternal stress (PNMS) has been operationalized variably as psychological distress (e.g., pregnancy‐specific anxiety or depressive symptoms) or stressful life events (e.g., bereavement, daily hassles), with evidence of associations with increased emotional, behavioral, and social problems in childhood (Lahti et al., ; Lin, Crnic, Luecken, & Gonzales, ; O'Connor, Heron, Golding, Beveridge, & Glover, ; Robinson et al., ). Nevertheless, despite these associations, conjecture remains concerning the mechanisms and moderators of the influence of PNMS on infant and child outcomes.…”
Section: Natural Disasters As “Natural Experiments”mentioning
confidence: 99%
“…Indeed, most studies examining the effects of PNMS on behavior during early childhood have done so using subjective measures of psychological stress and distress, such as symptoms of anxiety and depression or perceived impact of a life event (O'Connor, Heron, Golding, et al., ; Pickles, Sharp, Hellier, & Hill, ; Soe et al., ; Zhu et al., ). Studies finding an effect of more objective measures of PNMS (e.g., frequency of certain stressful life events) on child outcomes did not control for the appraisal or emotional distress associated with these experiences (Lin et al., ; Robinson et al., ; Ronald, Pennell, & Whitehouse, ). Furthermore, few studies have examined both aspects of the stress experience in the one cohort, and those that have sought to disentangle the objective from the subjective components of stress during pregnancy (Bergman, Sarkar, O'Connor, Modi, & Glover, ; Gutteling et al., ) have not yet identified a consistent pattern concerning the differential effects of these aspects of the stress experience, possibly due to their different measurement approaches.…”
Section: Natural Disasters As “Natural Experiments”mentioning
confidence: 99%
“…While this hypothesis is supported by some studies of behaviour in young children (Lin et al, 2017;H. Sharp et al, 2015), a number of studies find specific or stronger PNMS effects on behaviour for boys (Loomans et al, 2011;Zhu et al, 2015).…”
Section: Moderators Of the Effects Of Prenatal Maternal Stress On Chimentioning
confidence: 94%
“…where distress is expressed inwardly (i.e., anxiety and depressive problems) (V. E. Cosgrove et al, 2011;Krueger, 1999). A number of prospective cohort studies have found evidence of increased early childhood internalising problems following exposure to PNMS when assessed as a composite of prenatal maternal anxiety and depression symptoms, or global mental distress (de Bruijn, van Bakel, & van Baar, 2009;Kvalevaag et al, 2015), maternal anxiety (H. Sharp, Hill, Hellier, & Pickles, 2015) and frequency of stressful life events (Lin, Crnic, Luecken, & Gonzales, 2017;Robinson et al, 2008). Considering child anxiety symptoms separately using maternal interview, Bendiksen et al (2015) found increased risk of clinically significant problems in 3-year-old children of mothers reporting greater symptoms of maternal general distress prenatally.…”
Section: Internalising Problems Internalising Behavioural Problems Rmentioning
confidence: 99%
See 1 more Smart Citation